Confinement-Induced Growth of Au Nanoparticles Entrapped in Mesoporous TiO2 Thin Films Evidenced by in Situ Thermo- Ellipsometry - Martínez, Eduardo David (2014)
Metal-porous oxide nanocomposites present great interest in optical devices and heterogeneous catalysis. For these applications, particle shape and size control, as well as accessibility, are critical aspects. In this work, gold nanoparticles (NPs) were infiltrated into mesoporous TiO2 thin films (MTTF) by an impregnation-reduction method. In situ ellipsometry measurements were performed during thermal treatment to follow in real time the changes in the optical constants and thickness of the composites systems while being submitted to continuous heating at different rates, from room temperature up to 600 °C. Complementary characterization by UV–visible spectrophotometry, grazing incident wide angle scattering (GIWAXS), and X-ray reflectometry (XRR) were performed. TEM microscopy was used to analyze the morphological changes in the composite films after the thermal treatment. Our experiments demonstrate that particle coarsening starts at temperatures below 200 °C through the processes of ripening and particle migration, leading to changes in the particle size distribution (PSD) until a mechanical restriction, due to the porous geometry, induces a change of the particle shape from spherical to ellipsoidal. This results in an internal stress that swells the mesoporous film. The effect of the gold filling fraction and the heating ramp was analyzed. A mechanism based on the kinetics of particle migration and coalescence, through the modeling of the localized surface plasmon resonance under the dipolar approximation, is proposed to explain the changes in the optical properties of these composites materials and unravel the thermal activated processes occurring in metal crystallites supported on porous oxide frameworks.